Intumescence behaviour of bottom ash based geopolymer mortar through microwave irradiation – As affected by alkali activation. (15th November 2016) - Haq, Ehsan Ul; Padmanabhan, Sanosh Kunjalukkal; Zubair, Muhammad; Ali, Liaqat; Licciulli, Antonio
Highlights: Effect of alkali over foamability of bottom ash geopolymer is studied. Optimum alkali activation to tailor various properties. Alkali activation produces narrow pore size range, high strength and elastic moduli. Higher degree of geopolymerization is achieved in geopolymer foams. All claims are justified by characterization and related literature. Abstract: In this research the effect of alkali over the microwave enhanced bottom ash based geopolymer foam, is studied. Various samples using bottom ash and sodium silicate were prepared by varying the amounts of alkali. The higher amounts of alkali were compensated by reducing the sodium silicate percentages in order to keep the relative amounts of bottom ash and other ingredients constant. In the absence of alkali activation, the expansion in the slurry is more compared to alkali activated slurry but the porosity distribution is not so uniform as in the case of alkali activated geopolymer foam. Furthermore, a pipe also appeared in the center of non-alkali treated samples. The porosity was uniform in morphology and distribution from top to bottom for the alkali activated geopolymer foams hence properties as well. The increased amount of sodium hydroxide enhanced the properties till 5% by weight. The strength is found to be more by the use of alkali upto 3.15 MPa with 5% sodium hydroxide solution. The properties developed in the foams are justified by the TGA, DTA, FTIR and SEM analysis. Higher surface area was obtained for the samples without alkali activation compared to alkali activated samples.